A Comparative Study of Middle School Deaf Students’ Perceptions towards Vocational Internships According to Their Gender, Grade Level and Family Income at The Special Education School of Qujing, China - Yang, Liu; Ye, Yan (Scholar: Human Sciences, 2017)
The purpose of this study was to identify the demographic factors of the deaf students, to determine the deaf students’ perceptions towards vocational internships, and to compare the deaf students’ perceptions towards vocational internships at the Special Education School of Qujing according to gender, grade level and family income in 2015. A total of 147 deaf students (106 male and 41 female), from grade level 7 to vocational high school completed the survey. Statistical measures employed included frequency and percentage, mean and standard deviation, one-way ANOVA and independent samples t-test. The result of this study has indicated that gender difference was not a significant issue to impact students’ perceptions, yet the researcher discovered that students from different grade levels and different extents of family income had significant perception differences. Specifically, students from a higher grade level had higher perceptions than those from lower grade levels. In terms of family income, students from families whose monthly income was lower or included 1000 RMB had lower perceptions than other students. Recommendations for directors, teachers, the school, the students and future researchers are provided.